Pentanema kurdistanicum (Inuleae, Asteraceae), a new species from subalpine cliffs of Kurdistan, Iran - Maroofi, Hosein; Ghaderi, Hiva (Phytotaxa, 2016)
A new species of Pentanema, P. kurdistanicum is described and illustrated from Kurdistan, west of Iran. The new species was found scattered among rocks in the subalpine zone of S Marivan, in a low number of individuals. The new species is compared with the nearest allies, P. flexuosum and P. prasinurum. The phytochoria, morphological characters, ecology, conservation status, distribution map and phenology of the new species are presented.